Indonesia - Abdul Aziz; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Abstract The city of Cirebon is still experiencing limited cultural arts facilities, the Department of Youth, Sports, Culture and Tourism. the absence of an art and cultural forum has made visual artists and souvenir artisans unable to show off and market their work in a decent place. Organizing and marketing works of art regularly with good packaging, we consider it as one of the effective ways to increase people's appreciation of the variety of Cirebon art types and ethnic or regional art.. Cirebon is very well known for its art, apparently as glass painting and batik art, enabling art activists to hold quality and scheduled art performances. Cirebon must start thinking about the facilities or containers, arts and culture of Cirebon, so that the design of Cirebon cultural arts tourism, in order to accommodate its cultural arts, and be able to exhibit cultural arts, design of Cirebon cultural art tourism with a contemporary architecture approach will show the shape and appearance with a newer and more up-to-date style, agara can be an attraction for visitors and tourists